On the potential policy use of biodiversity indicators Limitations of some currently used indices at the country level based on the Hungarian example and recommendations for improvement - Zsófia Benedek (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
In order to facilitate the use of biodiversity indicators in policy making at the country level, a few and well-established indices should be suggested. Promising candidates include biodiversity-related indices of the Convention on Biological Diversity; therefore I evaluate their current use and performance in Hungary as a model country. Especially indices of the ecosystem level have already been in use, but they are not necessarily useful measures of the state of biodiversity in their current form. I recommend some improvements which may potentially increase their applicability. First, as not all the ecosystems suggested globally for monitoring (forests and marine habitats) are present in all the countries, the way of ecosystem selection should be standardized not the actual ecosystem types. Besides the information on the extent of some selected habitats, the original cover should also be considered to evaluate the present situation. In case of species-based indicators, the overlap between indices (e.g. involvement of birds in all of them) should be reduced. In the long run ecosystem-based indicators that account for ecosystem processes should be used in policy making instead of static lists as not biodiversity per se is important but the related ecosystem services.
Keywords: F53; Q23; Q57; 330; Indicator; Convention on Biological Diversity; environmental policy; policy making; ecosystem services; Hungary